2014
DOI: 10.1021/am5001773
|View full text |Cite
|
Sign up to set email alerts
|

Simple Way to Engineer Metal–Semiconductor Interface for Enhanced Performance of Perovskite Organic Lead Iodide Solar Cells

Abstract: A thin wide band gap organic semiconductor N,N,N',N'-tetraphenyl-benzidine layer has been introduced by spin-coating to engineer the metal-semiconductor interface in the hole-conductor-free perovskite solar cells. The average cell power conversion efficiency (PCE) has been enhanced from 5.26% to 6.26% after the modification and a highest PCE of 6.71% has been achieved. By the aid of electrochemical impedance spectroscopy and dark current analysis, it is revealed that this modification can increase interfacial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 35 publications
2
69
0
Order By: Relevance
“…These trends have been observed in hole conductor-free heterojunction perovskite solar cells, and recently, Habisreutinger et al also reported that direct con results in poor V oc and FF [33][34][35]. …”
supporting
confidence: 52%
“…These trends have been observed in hole conductor-free heterojunction perovskite solar cells, and recently, Habisreutinger et al also reported that direct con results in poor V oc and FF [33][34][35]. …”
supporting
confidence: 52%
“…Curiously, working devices have been obtained with comparable performances even when one carrier transport layer was omitted. Devices without a HTL have been reported by several groups [18,54,116,[126][127][128][129][130][131][132][133], for which it is claimed that the most commonly employed HTL, spiro-OMeTAD, is unnecessary and may be omitted from the device configuration as it is one of the more expensive components. Gold and silver electrodes are often applied for selective hole collection in most devices, however silver is becoming used less as it has proven to be chemically reactive with perovskite.…”
Section: The Planar Heterojunctionmentioning
confidence: 99%
“…This could be attributed to the fact that the thicker HTM prevents the direct contact between the Au electrode and the perovskite. [25] On the other hand, the PCE of the devices decrease the HTM thicknesses from 60 to 100 nm, which could be attributed to the higher series resistance caused by the thicker hole-transporting layer. [13] This result ascertained that suitable hole-transporting layer thickness has strong impact on the cell performance.…”
Section: Doi: 101002/aenm201600401mentioning
confidence: 99%